Students’ Assessment in Teaching Science and Technology - Viegas, Clara (2017)
Planning a thorough student assessment may produce good results in students’ learning. However, different aspects must be addressed in the course curriculum in order to foresee important features in the planning and implementation phases. This work presents the modifications carried out in a science course in engineering over three consecutive years, gradually incorporating important assessment to learn strategies identified in the literature. The results showed some crucial aspects of planning assessement in science/technology classes, in order to promote active learning and help students scaffold their knowledge. In accordance with teachers’ and students’ perceptions, some readjustments were made, creating a more demanding curriculum with positive learning and satisfaction outcomes.